MEA-based CO2 capture: a study focuses on MEA concentrations and process parameters - Wang, Nan; Wang, Dong; Krook-Riekkola, Anna; Ji, Xiaoyan (Frontiers in Energy Research, 2023)
CO2 capture using monoethanolamine (MEA) is one of the important decarbonization options and often considered as a benchmark, while the optimal MEA contraction and systematic process study are still lacking. In this work, firstly, the MEA concentrations between 15 and 30 wt% were studied from both process simulations with Aspen Plus and experimental measurements in the pilot-scale. 20 wt% MEA was identified as the preferable solution. Subsequently, a systematic analysis was conducted for CO2 capture using 20 wt% MEA with/without CO2 compression to study how various parameters, including gas flow rate, CO2 concentration, and CO2 removal rate, affected the energy demand and techno-economic performances quantitatively. The influence of each parameter on both energy demand and cost showed an obvious non-linear relationship, evidencing the importance of systematic analysis for further study on decarbonization. The evaluation indicated that the regeneration heat required the largest portion of energy demand. The economic analysis showed that the capital cost was more sensitive to the selected parameters than the operational cost, while the operational cost created a major change in the overall cost. In addition, the gas flow rate and CO2 concentration were the main parameters affecting the cost, rather than the CO2 removal rate. Finally, it was suggested that, for a new plant, CO2 capture showed the minimum investment cost per ton CO2 when operating the plant on a large scale, high CO2 concentration, and high CO2 removal rate; for an existing plant, the capture preferred to run with the high CO2 removal rate.